The consumption of pornography in university students - Canet Benavent, Encarna; Martínez Martínez, Lucía (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Recent research emphasizes the alarming consumption of mainstream pornography in adolescence The lack of sex education in the academic and family environment, lack of professional advice, and the lack of critical voices with this model of sexuality that is sold to adolescence, causes them to resort to fast consumer pornography as a mechanism for information and training on sex, considering the scenes he narrates as a role model In this communication, the objective is to know the reality of pornography consumption in university students of the Degree in Social Work of the University of Valencia.